(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the elections to the State Duma of Russia in Turkestan, representatives of the European population elected from the region, the membership of representatives of the European population to various factions, the commission elected to the Duma and the participation of representatives of the Turkestan region in it, speeches by deputies elected from the European population from the rostrum of the Duma, opposition to the government, the position of representatives on agrarian the question.